The level of efficiency in handling container traffic at Penang port: A simulation study - Saleh, Abdul Razak; Mat Tahar, Razman (Universiti Utara Malaysia, 1999)
The six-month period (January 1995 - June 1995) data was extracted from "Pelabuhan Kontena" (PELAKON) system and tested using SIMAN simulation process. Among the data available from the PELAKON system are: arrival time of a ship, departure time of a ship, operation time for loading and unloading, total number of equipment used, number of containers unloaded, number of containers loaded size of a ship, country of registration, last port of call, and next port of call. The arrival pattern of large ships (having a capacity to carry 507 or more containers) and small ship (having a capacity to carry less than 507 containers) follows Weibull distribution and Log-normal distribution, respectively.